2018
DOI: 10.1007/s10578-018-0800-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Comorbid Psychopathology and Conduct Problem Severity on Response to a Multi-component Intervention for Childhood Disruptive Behavior

Abstract: This study examined the effects of comorbid ADHD symptoms, internalizing psychopathology, Callous-Unemotional (CU) Traits, and conduct problem severity on children's response to an evidence-based psychosocial intervention. Clinic-referred children with DBD ages 8-12 years (N = 76) participated in a 15-week multi-component intervention. Parents provided weekly ratings of children's oppositionality-defiance, peer problems, and impairment. Oppositionality-defiance, peer problems, and impairment decreased signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In addition, the child component in SST has also been evaluated in showing reduced disruptive behavior, increased social competence and cognition, compared to control and reduced aggressive behavior and CU traits (Taylor et al 2017). SST has also been evaluated in a pre-post study on children with disruptive behavior disorders showing significant reduction of conduct disorder symptoms (Aitken et al, 2018) Results of the current study reveal that statistical significant differences were found regarding behavioral problems at post intervention. These results may be due to children are learned to appropriately interpret social cues, communicate effectively with others, make appropriate choices, generate more positive reactions, cope successfully , increase self -esteem and empowerment and avoid applying a hostile arrtibution bias that help them to demonstrate social and problem solving skills and reduce aggressive and antisocial behaviors.…”
Section: Tablementioning
confidence: 86%
“…In addition, the child component in SST has also been evaluated in showing reduced disruptive behavior, increased social competence and cognition, compared to control and reduced aggressive behavior and CU traits (Taylor et al 2017). SST has also been evaluated in a pre-post study on children with disruptive behavior disorders showing significant reduction of conduct disorder symptoms (Aitken et al, 2018) Results of the current study reveal that statistical significant differences were found regarding behavioral problems at post intervention. These results may be due to children are learned to appropriately interpret social cues, communicate effectively with others, make appropriate choices, generate more positive reactions, cope successfully , increase self -esteem and empowerment and avoid applying a hostile arrtibution bias that help them to demonstrate social and problem solving skills and reduce aggressive and antisocial behaviors.…”
Section: Tablementioning
confidence: 86%
“…These parents were invited to participate in this clinical trial following psychiatric assessment and referral for psychosocial treatment to a specialized clinic for children with disruptive behaviour. This is a secondary data analysis from the Addressing Behaviour and Treatment Effectiveness (ABATE) Project registered with ClinicalTrials.gov (Identifier: NCT02488499) (Aitken et al, 2018). This study was also approved by the Centre for Addiction and Mental Health's Research Ethics Board (Approval #: 091/2010).…”
Section: Participantsmentioning
confidence: 99%
“…Group-based CP is a manualized, highly accessible, and flexible to disseminate across hospital and community mental health contexts. Prior research supports CP as an effective treatment for children with DBD and co-occurring symptoms (Aitken et al, 2018). An excellent comparison for group-based CP is individualized treatment given its variability in clinician-driven personalized treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical guidelines call for the treatment of DBDs with APs adjunctively only after psychosocial and non-AP psychotropic medications have been applied (American Academy of Child and Adolescent Psychiatry [AACAP], 2009[AACAP], , 2011. Although several psychosocial interventions, including Triple-P and cognitive behavioral therapy have been shown to be effective at treating forms of DBD, the clinical guidelines calling for these therapies prior to prescribing are not universally followed (Aitken et al, 2018;Daviss et al, 2016;Ghosh et al, 2017;Leathers et al, 2021;Patel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%